2018
DOI: 10.1371/journal.pone.0208448
|View full text |Cite
|
Sign up to set email alerts
|

Why do psychiatric patients attend or not attend treatment groups in the community: A qualitative study

Abstract: BackgroundNon-attendance of treatment groups in the community has been a long-standing problem in mental health care. It has been found to have financial ramifications for services, worsen outcomes for those that do not attend and negatively impact on therapeutic group processes. There is a need to gain a better understanding of patients’ reasons for attending or not attending. This study aimed to explore patient views on facilitators and barriers to the attendance of treatment groups in the community.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…In addition, this was a small exploratory study, due to its circumscribed setting to a narrow geographical area of the United Kingdom and small number of potential participants (group attendees). Our findings, however, do mirror the general themes arising from a larger study conducted in the community (Dilgul et al, 2018), supporting the constructive paradigm adopted in our stance for data analysis. Inpatient…”
Section: Study Strengths and Limitationssupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, this was a small exploratory study, due to its circumscribed setting to a narrow geographical area of the United Kingdom and small number of potential participants (group attendees). Our findings, however, do mirror the general themes arising from a larger study conducted in the community (Dilgul et al, 2018), supporting the constructive paradigm adopted in our stance for data analysis. Inpatient…”
Section: Study Strengths and Limitationssupporting
confidence: 81%
“…To our knowledge, this is the first contemporary qualitative study in the United Kingdom that has been conducted in order to explore service users' perspectives on non-engagement with psychological therapy groups in the inpatient setting. We are only aware of one prior larger study with similar aims conducted by our research group, albeit focussing specifically on community-based groups (Dilgul et al, 2018). Themes identified in the present study were in line with those identified previously, including the need for service users to be informed about the groups, interactions with other participants and the crucial role of maintaining a safe environment.…”
Section: Study Strengths and Limitationssupporting
confidence: 76%
See 2 more Smart Citations
“…There may be several reasons for the low drop-out rate in the current study, including the ‘opt-in’ nature of the way the mindfulness group was offered, and the opportunity to try an orientation ‘taster’ session first. The importance of encouraging service user choice and a feeling of autonomy has been previously highlighted as a facilitating factor which promotes regular group attendance in a qualitative study of 67 people who had attended therapy groups in the community [ 40 ].…”
Section: Discussionmentioning
confidence: 99%